Develop and Evaluate Teaching-Learning Materials Using the Learning Management System (LMS) - THOUMMALY, Sommith; Vongpasith, Phouthone; Lusavong, Sommany; Banchong, Soukpaseuth; Phonhdala, Phonepaseuth (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research paper was created to develop and evaluate online teaching-learning materials by conducting a test with 66 students, which was divided into two groups: The first group is first year students of Program Development, Faculty of Natural Sciences, National University of Laos, and the second group is second year students in Computer Engineering, Faculty of Engineering, Suphanuvong University. The research is divided two parts. Part 1 studied the behavior and attitudes of the sample in the use of online teaching-learning materials using basic statistics by finding averages, standard deviations, and percentages. and the Part 2 compares the learning outcomes before and after using online learning-teaching materials with Linear Regression method. The results of Part 1 research showed that students' satisfaction with each of the online teaching-learning materials was good, with an average of 3.95, 3.80, 3.94, 3.94, 3.64 and 4.06 in terms of content, design, teaching staff, and facilities, respectively (maximum score of 5). Section 3 The results of the study show that the learning outcomes of the students improved after the use of online teaching-learning materials with the average value before and after the use of online teaching-learning materials of the group of students of Suphanuvong University and the group of students of the National University of Lao was 34.64, 53.21 and 45.54, 67.00 respectively. The results of the study also know that tracking student enrollment is an important factor and has a positive effect on post-enrollment test scores in online learning-teaching materials.